Optimalisasi Pengelolaan Keuangan Masjid Melalui Digitalisasi Berbasis Prinsip Syariah Studi Kasus Masjid Ar-Rohmah - Emiliana Rachma; Ade Gunawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
The project-based Field Experience Program (PPL) at the Ar-Rohmah Mosque was implemented as a form of community service aimed at optimizing the mosque's financial management system to make it more structured, transparent, and accountable. This activity utilized interviews, observations, and participatory discussions with administrators to uncover real-world needs. The activity included preparation, project implementation, monitoring and guidance, coordination with partners, report preparation and evaluation, and presentation of project results to the supervising lecturer and partners.The results demonstrated that students were able to design a simple digital-based financial report template using Microsoft Excel, assist the treasurer in its use, and compile a final report that can serve as a guideline for sustainable mosque financial management. The activity also successfully documented the entire process, including daily reports, photos, and videos, providing evidence of program implementation. Partners' active participation was evident at every stage, from planning to evaluation, demonstrating the community's full involvement in supporting the project's success. In addition to producing technical output in the form of a financial recording system, this activity also has social impacts, namely increased awareness of the congregation regarding the importance of transparency, the growth of management behavior that is more meticulous in financial recording, and the emergence of local leaders who play a role in the implementation of the new system. Thus, this project-based PPL activity is not only beneficial for partners, but also serves as a learning tool for students to apply knowledge in the community, while simultaneously encouraging social transformation towards better mosque governance.